Fostering Renewables into the Cold Chain: How Photovoltaics Affect Design and Performance of Refrigerated Automated Warehouses - Antonella Meneghetti; Fabio Dal Magro; Patrizia Simeoni (Energies, 2018)
In the industrial food supply chain, cold storage is one of the most important processes where there is a huge but still unused potential for employing renewable energy technologies. This paper analyses how the integration of rooftop photovoltaics affects the design and performance of refrigerated automated warehouses, which are becoming the preferred choice for frozen food storage facilities. The problem is modelled and solved by means of Constraint Programming. Results for the reference case in north-eastern Italy show that photovoltaic installation can lead to both yearly total cost and energy savings. Simulations highlight how design and performance of the refrigerated automated warehouse strictly depend on supply chain decision variables. PV integration offers supply chain managers more opportunities to act on the storage temperature and the incoming product temperatures strictly related to upstream and downstream stages of the whole cold chain. Attention should be paid to system throughput, which presents an intermediate range for which the design optimization of volume and surfaces reduces the convenience of PV integration. Simulations on facility locations reveal how different climate conditions affect the economic and environmental performance of the refrigerated warehouse, as well as country specific carbon intensity and energy price.